A compact trisection microstrip bandpass filter with frequency-dependent cross-coupling. Issue 7 (3rd October 2017) - Wu, X. H.; Wei, X. B.; Lv, H. G.; Shi, Y.
ABSTRACT: A compact microstrip bandpass filter using stub loaded ring resonators and double-loop ring resonators in an embedded triplet configuration with frequency-dependent cross-coupling is proposed in this article. The embedded triplet configuration is realized by putting the loops of the double-loop ring resonator into the circles of the stub loaded ring resonators. The frequency-dependent cross-coupling has been introduced to the filter by a manner of separate electric- and magnetic-coupling path. Three transmission zeros are obtained to enhance the frequency selectivity and stopband performance. Among them, two are achieved by the frequency-dependent cross-coupling, the other one is created by the harmonic effect of the transmission lines. The filter is designed for 2.4 GHz Wireless Local Area Networks application with 20.8% fractional bandwidth. The measured results show reasonable agreement with the simulated ones.